Combination of Endothelial-Monocyte-Activating Polypeptide-II with Temozolomide Suppress Malignant Biological Behaviors of Human Glioblastoma Stem Cells via miR-590-3p/MACC1 Inhibiting PI3K/AKT/mTOR Signal Pathway - Zhou, Wei; Liu, Libo; Xue, Yixue; Zheng, Jian; Liu, Xiaobai; Ma, Jun; Li, Zhen; Liu, Yunhui (Frontiers in Molecular Neuroscience, 2017)
This study aims to investigate the effect of Endothelial-Monocyte-Activating Polypeptide-II (EMAP-II) combined with temozolomide (TMZ) upon glioblastoma stem cells (GSCs) and its possible molecular mechanisms. In this study, combination of EMAP-II with TMZ inhibited cell viability, migration and invasion in GSCs, and autophagy inhibitor 3-methyl adenine (3-MA) and chloroquine (CQ) partly reverse the anti-proliferative effect of the combination treatment. Autophagic vacuoles were formed in GSCs after the combination therapy, accompanied with the up-regulation of LC3-II and Beclin-1 as well as the down-regulation of p62/SQSTM1. Further, miR-590-3p was up-regulated and MACC1 was down-regulated by the combination treatment in GSCs; MiR-590-3p overexpression and MACC1 knockdown up-regulated LC3-II and Beclin-1 as well as down-regulated p62/SQSTM1 in GSCs; MACC1 was identified as a direct target of miR-590-3p, mediating the effects of miR-590-3p in the combination treatment. Furthermore, the combination treatment and MACC1 knockdown decreased p-PI3K, p-Akt, p-mTOR, p-S6 and p-4EBP in GSCs; PI3K/Akt agonist insulin-like growth factor-1(IGF-1) partly blocked the effect of the combination treatment. Moreover, in vivo xenograft models, the mice given stable overexpressed miR-590-3p cells and treated with EMAP-II and TMZ had the smallest tumor sizes, besides, miR-590-3p+EMAP-II +TMZ up-regulated the expression level of miR-590-3p, LC3-II and Beclin-1 as well as down-regulated p62/SQSTM1. In conclusion, these results elucidated a novel molecular mechanism of EMAP-II in combination with TMZ suppressed malignant biological behaviors of GSCs via miR-590-3p/MACC1 inhibiting PI3K/AKT/mTOR signaling pathway, and might provide potential therapeutic approaches for human GSCs.